The Concept of "Fast Track Surgery" as an Influencer on the Dynamics of Components of Stress-Realizing and Stress-Limiting Systems in the Perioperative Period - Gerbali, Oksana Yu.; Gumenyuk, Lesya N.; Sarchuk, Elena V.; Kerimov, Enver Ya.; Karakursakov, Nariman E. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The concept of "Fast Track Surgery" has been of increasing interest, which implies accelerated recovery and a decrease in the frequency of postoperative complications, namely, a decrease in the body’s stress response to surgery. The study aimed to assess the effect of Fast Track Surgery on the degree of surgical treatment trauma based on the dynamics of the functional integration of hormonal components of the stress-realizing / stress-limiting systems in the perioperative period. The study was conducted in 3 groups of patients. Groups of patients are comparable in age, sex, diagnosis of an underlying disease, degree of operative-anaesthetic risk ASA, intraoperative parameters, which allowed to carry out an analytical evaluation of the results of the study as objectively and reliably as possible. In the postoperative period, the maximum increase in stress-realizing system parameters in all groups was registered in patients after 1 day after surgery, less significant after LSSI-F: the concentration of daily excretion of dopamine exceeded the preoperative values by 1.2 times, epinephrine 2.0 times, norepinephrine in 1.3 times. Along with the activation of the stress-realizing system, a dynamic increase in the activity of the stress-limiting system was noted: after LSSI-F, the level of GABA increased by 1.3 times, after TSSI, the GABA secretion increased 1.2-fold. Laparoscopic SSI in combination with "Fast Track Surgery" contributed to a decrease in the intensity of the patient’s stress response to the operating injury, which, in turn, significantly increased the effectiveness of simultaneous treatment and the quality of life of patients.